Drivers of fine‐scale diurnal space use by a coral‐reef mesopredatory fish. Issue 4 (18th February 2022) - Harborne, Alastair R.; Kochan, David P.; Esch, Melanie M.; Fidler, Robert Y.; Mitchell, Matthew D.; Butkowski, Drew W.; González‐Rivero, Manuel
Abstract: The habitat preferences of many reef fishes are well established, but the use of space within these habitats by non‐site‐attached species is poorly studied. The authors examined the space use of a functionally important mesopredator, graysby ( Cephalopholis cruentata ), on six patch reefs in the Florida Keys. A 1 m 2 ‐scale grid was constructed on each reef and 16 individual C. cruentata were tracked diurnally in situ to identify space use. At the patch reef scale, larger C. cruentata were more active and had larger observed home ranges, although home ranges were also affected by fish density and the abundances of prey and predators. The total time in each 1 m 2 grid cell was regressed against a range of fine‐scale biotic variables, including multiple variables derived from structure‐from‐motion three‐dimensional digital reconstructions of each reef. Nonetheless, time in grid cells (preferred microhabitats) was only significantly positively correlated with the height of carbonate structures, likely because the cavities they enclose are particularly suitable for predator avoidance, resting and ambushing prey. The ongoing flattening of reefs in the region caused by negative carbonate budgets is thus likely to have significant effects on the abundance and space use of C. cruentata . In addition to examining spatial patterns, we analysed C. cruentata waiting times in each grid cell before moving. These times were best approximated by a truncated power‐law (heavy‐tailed) distribution, indicating a "bursty" pattern of relatively long periods of inactivity interspersed with multiple periods of activity. Such a pattern has previously been identified in a range of temperate ambush predators, and the authors extend this move‐wait behaviour, which may optimize foraging success, to a reef fish for the first time. Understanding how C. cruentata uses space and time is critical to fully identify their functional role and better predict the implications of fishing and loss of reef structure.